Investigations on the adaptability of wireless sensor networks (WSN) based technology for harvesting crops - Ayisha Mangat (Department of Farm Power Machinery and Energy, Kelappaji College of Agricultural Engineering and Technology, 2016)
Harvesting has been identified as one of the critical and resource consuming operation because of several reasons especially inside polyhouse structures. Knowledge of physical properties of crops and fruits like cucumber plays an important role in the design and optimization of its machinery. Evaluation of these properties like plant height, leaf numbers, leaf length, leaf width, fruit length and width were taken for observation. It was seen that, these properties had a direct impact on deciding the components of the harvester. Plant height determined the height of the harvester; leaf parameters decided the obstacle parameters in the work space. Fruit holding capacity of the cutting unit was depended on fruit parameters. By analyzing all these data and the past work in the field of robotics, a preliminary model of a harvester was fabricated. Out of the harvesters developed so far in the field of agriculture, the most simple and economical method was selected for this study. The principle of linear actuators was adapted for the design of the harvester by incorporating screw rods and DC motors. The basic components for the harvester were identified with three Degrees of Freedom. The moving unit with wheels contributes to the motion in X direction. The vertical screw thread makes the movement in Y direction and the horizontal unit gives the motion in Z direction. By studying the biometric properties of plants and crops, the height of the harvester was confined to 2 m, width of horizontal unit as 45 cm and the base platform with 45X45 cm. A control board was used for controlling the motors which causes motion for the threaded rods. Accordingly, a laboratory model was fabricated and its functionality was tested. It was found working successfully in the laboratory conditions. The current trend in high-tech agriculture is towards switching from a manual system to automatic operations. Hence, the present study is a promising technology that can be converted to a fully automatic machine with future developments.